In vitro rescue of FGA deletion by lentiviral transduction of an afibrinogenemic patient's hepatocytes. (1st October 2014) - Stroka, D.; Keogh, A.; Vu, D.; Fort, A.; Stoffel, M. H.; Kühni‐Boghenbor, K.; Furer, C.; Banz, V.; Demarmels Biasiutti, F.; Lämmle, B.; Candinas, D.; Neerman‐Arbez, M.
Summary Background Congenital afibrinogenemia is a rare inherited autosomal recessive disorder in which a mutation in one of three genes coding for the fibrinogen polypeptide chains Aα, Bβ and γ results in the absence of a functional coagulation protein. A patient with congenital afibrinogenemia, resulting from an FGA homozygous gene deletion, underwent an orthotopic liver transplant that resulted in complete restoration of normal hemostasis. The patient's explanted liver provided a unique opportunity to further investigate a potential novel treatment modality. Objective To explore a targeted gene therapy approach for patients with congenital afibrinogenemia. Methods and Results At the time of transplant, the patient's FGA‐deficient hepatocytes were isolated and transduced with lentiviral vectors encoding the human fibrinogen Aα‐chain. FGA‐transduced hepatocytes produced fully functional fibrinogen in vitro. Conclusions Orthotopic liver transplantation is a possible rescue treatment for failure of on‐demand fibrinogen replacement therapy. In addition, we provide evidence that hepatocytes homozygous for a large FGA deletion can be genetically modified to restore Aα‐chain protein expression and secrete a functional fibrinogen hexamer.